HEALTH EDUCATION TEACHING STUDENTS OF STOMATOLOGYCAL FACULTY UNDER THE STUDY COURSE PROPAEDEUTICS OF INTERNAL MEDICINE - Оринчак, М. А.; Вірстюк, Н. Г.; Човганюк, О. С.; Василечко, М. М.; Гаман, І. О.; Артеменко, Н. Р.; Вакалюк, І. І.; Александрук, Д. П.; Краснопольський, С. З. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Health education is an important part of preventive medical doctor in any specialty. Therefore, teaching health education at the present stage of development of higher medical education should be conducted in all clinical, hygienic and theoretical departments. The main purpose of this notice is to improve the quality of teaching health education at the departments of internal medicine by the formation of teachers and students appropriate attitudes and awareness of the importance of studying specific issues of health education of the stomatological faculty students during lectures and practical lessons on selected sections of internal medicine. The main tasks of teaching health education in the course propaedeutics internal medicine include are formation of students’ beliefs in the necessity and importance of health education in the overall treatment and prevention of disease; familiarization with the organization of health education in the hospital, clinics and dispansaries in each situation of physician according to the subject lessons or lectures. Moreover, the course propaedeutics internal medicine must disclose the value of health education in preventive activities all together. It is necessary to form the students’ practical skills distribution among the population hygienic knowledge on all sections of hygiene, nutrition, housing, work, social and personal care, explain the harmful influence of alcohol, smoking, learning the basics of first aid in case of accidents, injuries, poisoning, burns, frostbite and diseases. When studying selected sections of propaedeutics internal medicine students must master certain specific techniques, skills in disease prevention, increase the level of hygiene, maintaining health, increasing the duration and improve the quality of life.